2018
DOI: 10.1111/tpj.14073
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of SlARF10A dosage by sly‐miR160a is critical for auxin‐mediated compound leaf and flower development

Abstract: miR160 adjusts auxin-mediated development by post-transcriptional regulation of the auxin response factors ARF10/16/17. In tomato, knockdown of miR160 (sly-miR160) suggested that it is required for auxin-driven leaf blade outgrowth, but whether additional developmental events are adjusted by sly-miR160 is not clear. Here, the SlMIR160 genes and the genes of its SlARFs targets were edited by CRISPR/Cas9 resulting in the isolation of loss-of-function mutants. In addition, hypomorphic mutants that accumulate vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 58 publications
4
36
0
Order By: Relevance
“…ARF10 was also suggested to be the major target in tomato. 33 Even though we could detect miR160-targeted cleavage products of StARF16 through RLM-RACE technique, the expression of StARF16 was not complementary to that of miR160 in our transgenic plants. This atypical miR160-ARF16 expression pattern was also reported in tomato 15 suggesting a complex regulation of ARF16 expression by factors other than miR160.…”
Section: Mir160-targeted C-arfs Modulate Auxin Sensitivitymentioning
confidence: 76%
See 1 more Smart Citation
“…ARF10 was also suggested to be the major target in tomato. 33 Even though we could detect miR160-targeted cleavage products of StARF16 through RLM-RACE technique, the expression of StARF16 was not complementary to that of miR160 in our transgenic plants. This atypical miR160-ARF16 expression pattern was also reported in tomato 15 suggesting a complex regulation of ARF16 expression by factors other than miR160.…”
Section: Mir160-targeted C-arfs Modulate Auxin Sensitivitymentioning
confidence: 76%
“…It is proposed that different expression levels of C-ARFs results in variable degree of leaf complexity in tomato. 33 Hence, the leaf compounding phenotypes of our potato plants could be attributed to the extent of miR160 overexpression or knockdown.…”
Section: Mir160 and Its Targets Are Crucial Regulators Of Final Leaf Shape In Potatomentioning
confidence: 90%
“…In addition, overexpression of miR160 gene under a constitutive CaMV‐35S promoter in tomato resulted in an entire leaflet blade phenotype compared to the wild‐type leaves. Meanwhile the expression level of the tomato Knotted 2 protein (Tkn2) was negatively correlated with miR160 levels and positively correlated with ARF gene expression levels, such as ARF16 (Damodharan et al ., 2018). Consistently, in our study, expression of a miR160‐resistant GhARF16 gene in Arabidopsis and cotton led to significantly increased GhKNOX2‐1 transcripts and deeply serrated leaf margins.…”
Section: Discussionmentioning
confidence: 99%
“…Hormone signaling pathways play an essential role in coordinating multiple developmental programs including the germination process, organ morphogenesis, and floral transition in response to various environmental conditions [62]. The latest studies demonstrated that some miRNAs act as a key regulator of auxin signaling pathway and directly or indirectly affect floral transition in different plant species [63][64][65]. Similarly, miR390 and miR393 are involved in controlling the auxin signaling pathway to influence such actions of plants [66][67][68].…”
Section: Micrornas and Plant Developmentmentioning
confidence: 99%